2017
DOI: 10.1002/acp.3345
|View full text |Cite
|
Sign up to set email alerts
|

Empathy's Relation to Appraisal of the Emotional Child Witness

Abstract: When observing others, we often try to determine how they 'really feel' deep down inside (emotional feeling) regardless of their outward expression (emotional appearance). We examined whether child victim empathy predicts appraisal of a child sexual assault victim's emotional feelings and, in turn, child and defendant believability and verdict decisions. Undergraduates (N = 50) rated photographs of 5-and 13-year-olds' degree of sadness. Then, a new group of undergraduates (N = 354), randomly assigned within a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…This effect was independent of the presentation mode of the testimony; the same pattern of results was found comparing video and audio recordings with written transcripts that noted the child's emotional reaction . Landström et al (2015) confirmed the child emotional witness effect in two experiments with video recordings of the children's testimony whereas Bederian-Gardner et al (2017) failed to observe a direct effect of emotional display on child victim believability with (less informative) still pictures of the witnesses. Castelli and Goodman (2014) reported that US prosecutors were more likely to file charges when the child's behavior during disclosure was rated as emotional than when it was rated as neutral.…”
mentioning
confidence: 83%
“…This effect was independent of the presentation mode of the testimony; the same pattern of results was found comparing video and audio recordings with written transcripts that noted the child's emotional reaction . Landström et al (2015) confirmed the child emotional witness effect in two experiments with video recordings of the children's testimony whereas Bederian-Gardner et al (2017) failed to observe a direct effect of emotional display on child victim believability with (less informative) still pictures of the witnesses. Castelli and Goodman (2014) reported that US prosecutors were more likely to file charges when the child's behavior during disclosure was rated as emotional than when it was rated as neutral.…”
mentioning
confidence: 83%
“…In order to assess the methodological quality of the instruments, we used the COSMIN (COnsensus‐based Standards for the selection of health Measurement INstruments) taxonomy and its recently developed Risk of Bias checklist for systematic reviews of Patient Reported Outcome Measurement instruments (PROMs) (Bederian‐Gardner et al ., ; Mokkink et al ., , ; Prinsen et al ., ). Although the COSMIN initiative mainly focuses on PROMs, the (adapted) methodology can also be used for other types of measurement instruments (Prinsen et al ., ).…”
Section: Methodsmentioning
confidence: 98%
“…From the literature on CSA cases in the legal field, we know that children's and adolescents' nonverbal emotional signs are frequently taken into account by professionals such as judges or prosecutors, as well as by jurors. Emotional signs, such as the child's or the adolescent's facial expressions during or after a verbal disclosure of sexual abuse in court, are often used to judge perceived credibility or the veracity of the allegations of CSA (Bederian‐Gardner and Goldfarb, ; Bederian‐Gardner et al ., ; Cooper, ; Katz et al ., ; Regan and Baker, ).…”
Section: Introductionmentioning
confidence: 99%